2000
DOI: 10.1046/j.1529-8817.2000.99106.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGENY OF THE CONJUGATING GREEN ALGAE (ZYGNEMOPHYCEAE) BASED ON rbc  L SEQUENCES

Abstract: Sequences of the gene encoding the large subunit of RUBISCO (rbcL) for 30 genera in the six currently recognized families of conjugating green algae (Desmidiaceae, Gonatozygaceae, Mesotaeniaceae, Peniaceae, and Zygnemataceae) were analyzed using maximum parsimony and maximum likelihood; bootstrap replications were performed as a measure of support for clades. Other Charophyceae sensu Mattox and Stewart and representative land plants were used as outgroups. All analyses supported the monophyly of the conjugatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
117
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 59 publications
12
117
2
3
Order By: Relevance
“…Not surprisingly, the first assessment with the molecular tools confirmed the anticipated monophyly of the class (BhattacharYa et al 1994, Besendahl & BhattacharYa 1999, Mccourt at al. 2000, Gontcharov et al 2003.…”
Section: Monophyly Of the Classmentioning
confidence: 93%
See 3 more Smart Citations
“…Not surprisingly, the first assessment with the molecular tools confirmed the anticipated monophyly of the class (BhattacharYa et al 1994, Besendahl & BhattacharYa 1999, Mccourt at al. 2000, Gontcharov et al 2003.…”
Section: Monophyly Of the Classmentioning
confidence: 93%
“…Ultrastructural studies in the conjugates revealed cytokinesis by a phragmoplast allying them with the Charales, Coleochaete, a few other algal taxa and embryophyte plants (Fowke & Pickett-heaPs 1969a, b, Pickett-heaPs 1975, Mattox & stewart 1984, GroliG 1992. Further biochemical and molecular data has shown an advanced position of the class Zygnematophyceae among streptophyte algae but were not conclusive regarding its exact placement there because their results were affected by insufficient taxon sampling, weak resolving power of the markers used or long-branch attraction artefact (kranz & huss 1996, BhattacharYa & Medlin 1998, chaPMan et al 1998, Qiu & PalMer 1999, Mccourt et al 2000.…”
Section: Phylogylogenetic Position Within Streptophytamentioning
confidence: 99%
See 2 more Smart Citations
“…(2015), but with 50 µl of Instagene Matrix instead of 100 µl (Bio-Rad Laboratories, USA). Primers RH1 and 1385R (McCourt et al ., 2000), and newly designed primers ZygF (5’TATGTCAACCACAAAC3’) and ZygR (5’GTATCAAATTCAAATTTA3’), were used for amplification of the rbc L gene in reactions containing 13.9 µl of sterile Milli-Q water, 2 µl of MgCl 2 (25 mM), 2 µl of AmpliTaq Gold 360 Buffer (Applied Biosystems, Carlsbad, California, USA), 0.4 µl of dNTP mix (10 mM), 0.25 µl of forward and reverse primer (25 pmol ml –1 ), 0.2 µl of AmpliTaq Gold 360 DNA Polymerase and 1 µl of DNA (10 ng µl –1 ). Cycling was performed with an initial denaturation for 10 min at 95°C, followed by 35 amplification cycles of 1 min denaturation at 94°C, 1 min annealing at 48°C and 2.5 min extension at 72°C, and a final extension at 72°C for 10 min.…”
Section: Dna Isolation Pcr and Phylogenetic Analysesmentioning
confidence: 99%